NILAI TUNJUK AJAR MELAYU DALAM TRADISI LISAN ONDUO PASIR PENGARAIAN KABUPATEN ROKAN HULU - Harry Persada; Rita Arianti (Universitas Batanghari, 2026)
This study aims to explore and analyze the values of Tunjuk Ajar Melayu (Malay Teaching and Advice) contained in the Onduo oral tradition in Pasir Pengaraian, Rokan Hulu Regency. As a form of intangible cultural heritage, Onduo functions not only as a lullaby for children but also plays a strategic role as a medium for transmitting moral, ethical, and religious messages within the Malay community. This research employs a qualitative approach with a descriptive method, collecting data through observation, interviews, and lyric documentation. The results indicate that 28 Onduo lyrics contain 15 types of Tunjuk Ajar Melayu values, including: 1) Belief in God Almighty (1 datum), 2) Obedience to parents (1 datum), 3) Unity and cohesion (1 datum), 4) Hard work, diligence, and persistence (1 datum), 5) Doing and reciprocating kindness (1 datum), 6) Responsibility (1 datum), 7) Shyness/Modesty (1 datum), 8) Compassion (2 data), 9) Respect and Prudence (1 datum), 10) Humility (3 data), 11) Having good prejudices towards others (2 data), 12) Self-awareness (8 data), 13) Forgiveness and generosity (1 datum), 14) Trustworthiness (2 data), and 15) Foresight (1 datum). These values are integrated into the lyrics through nature metaphors and local dialects that reflect the wisdom of the Rokan Hulu people. This study confirms that the Onduo oral tradition serves as a highly relevant character education instrument to safeguard the younger generation against the impacts of modernization. Thus, this study provides a significant contribution to preserving oral literature while documenting the noble values that serve as a life compass for the Malay community in Rokan Hulu.The conclusion of this research is that the Onduo oral tradition in Pasir Pengaraian, Rokan Hulu Regency, is not merely a vocal art for putting children to sleep, but a medium for transmitting the noble values of Tunjuk Ajar Melayu (Malay Teachings) that are crucial for character education. Onduo functions as a compass for life, documenting the noble values of the Malay community in Rokan Hulu. The existence of Tunjuk Ajar Melayu values in every lyric emphasizes that this tradition is a vessel for the moral, ethical, and spiritual formation of the younger generation.